On the mechanism underlying the divergent retinal and bristle defects of M8* (E(spl)D) in Drosophila. - Kahali, B.; Bose, A.; Karandikar, U.; Bishop, C.P.; Bidwai, A.P. (genesis, 2009)
Our results, using endogenous mutants and Gal4-UAS driven transgenes, implicate multisite phosphorylation in repression by E(spl)M8. We propose that these phosphorylations occur in the morphogenetic furrow (MF) to reverse an auto-inhibited state of M8, enabling repression of Atonal during R8 specification. Our studies address the paradoxical behavior of M8*, the truncated protein encoded by E(spl)D. We suggest that differences in N signaling in the bristle versus the eye underlie the antimorphic activity of M8* in N(+) (ectopic bristles) and hypermorphic activity in N(spl) (reduced eye). Ectopic M8* impairs eye development (in N(spl)) only during establishment of the atonal feedback loop (anterior to the MF), but is ineffective after this time point. In contrast, a CK2 phosphomimetic M8 lacking Groucho (Gro) binding, M8SDDeltaGro, acts antimorphic in N(+) and suppresses the eye/R8 and bristle defects of N(spl), as does reduced dosage of E(spl) or CK2. Multisite phosphorylation could serve as a checkpoint to enable a precise onset of repression, and this is bypassed in M8*. Additional implications are discussed.